The Mediating Effect of Organizational Citizenship Behaviour on the Relationship between Perceived Organizational Support and Turnover Intention: A Proposed Framework - Saoula, Oussama; Johari, Husna (International Review of Management and Marketing, 2017)
Employees' turnover is an international phenomenon that is deliberated as tough challenge to the companies, as it is tiring and costly. Thus there is obligation for conducting more researches in order to support the academicians, practitioners, decision makers with better understanding of this dilemma and clarify more on the factors affecting these phenomena in deferent settings and contexts of research, particularly in the non-western perspectives such as Malaysia who is facing a big challenge toward the employees' turnover in many sectors. Therefore, the purpose of this paper is determine the relationship between perceived organizational support, organizational citizenship behavior (benefiting the individual OCB-I, and benefiting the organization OCB-O) and turnover intention. Due to that, this study proposed framework to study the effect of perceived organizational support on turnover intention through the mediation role of organizational citizenship behavior (OCB-I, OCB-O). In addition, the direct effect between the variables has been discussed. . Hence this paper is expected to fill the research gap and contribute to the body of knowledge in this area of research. Keywords: Perceived Organizational Support, Organizational Citizenship Behavior (OCB-I, OCB-O), Turnover Intention, Social Exchange Theory JEL Classifications: M510, M520, M500